PENGARUH KOMPETENSI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT POS INDONESIA (PERSERO) CABANG SURAKARTA - Andika Sulistyo Rini, Istiatin & Eny Kustiyah (Universitas Slamet Riyadi, 2018)
This research intends to test competence, motivation and influence of work environment on performance of employees of PT Pos Indonesia (Persero) Cabang Surakarta. The population is taken all employees totalling 170 and sample as much of the 43 respondents with spread questionnaire. Hypothesis testing using multiple linear regression analysis. The questionnaire items tested has been declared valid and reliability. Classical assumptions in this research generates data which is normal, no multicollinearity and heterokedastisitas does not occur. Variable competence, motivation and work environment effect simultaneously and significantly to the performance of the employees with a value Fhitung 8,509 > Ftabel 2,84 significantly 0,000 < 0,05. The t-test with variable competence (X1) positive and significant effect on performance of employees with the results thitung 2,092 > ttabel 2,022 significantly 0,043 < 0,05. Motivational variables (X2) but not significant effect on performance of employees with a value of thitung 0,087 < ttabel 2,022 significantly 0,931 > 0,05. Environment variables work (X3) a positive and significant effect on performance of employees with a value thitung 2,275 > ttabel 2,022 significantly 0.028 < 0.05.Keywords: competence, motivation, work environment, performance